Elevated Incidence of Fractures in Solid-Organ Transplant Recipients on Glucocorticoid-Sparing Immunosuppressive Regimens - B. J. Edwards; A. Desai; J. Tsai; H. Du; G. R. Edwards; A. D. Bunta; A. Hahr; M. Abecassis; S. Sprague (Journal of Osteoporosis)
This study was conducted to assess the occurrence of fractures in solid-organ transplant recipients. Methods. Medical record review and surveys were performed. Patients received less than 6 months of glucocorticoids. Results. Of 351 transplant patients, 175 patients provided fracture information, with 48 (27.4%) having fractured since transplant (2–6 years). Transplants included 19 kidney/liver (50% male), 47 kidney/pancreas (53% male), 92 liver (65% male), and 17 pancreas transplants (41% male). Age at transplant was 50.8±10.3 years. Fractures were equally seen across both genders and transplant types. Calcium supplementation (n=94) and bisphosphonate therapy (n=52) were observed, and an association with a lower risk of fractures was noted for bisphosphonate users (OR=0.45 95% C.I. 0.24, 0.85). Fracture location included 8 (16.7%) foot, 12 (25.0%) vertebral, 3 (6.3%) hand, 2 (4.2%) humerus, 5 (10.4%) wrist, 10 (20.8%) fractures at other sites, and 7 (14.6%) multiple fractures. The estimated relative risk of fracture was nearly seventeen-times higher in male liver transplant recipients ages 45–64 years compared with the general male population, and comparable to fracture rates on conventional immunosuppressant regimens. Conclusion. We identify a high frequency of fractures in transplant recipients despite limited glucocorticoid use.